IDENTIFICATION GASTROINTESTINAL PARASITES IN THE SMALL INTESTINE, LARGE INTESTINE, AND FECES OF LOCAL PIG FROM NORTH SULAWESI - Kezia Andries; Revolson Alexius Mege; Nonny Manampiring (Indonesian Biodiversity Journal, 2021)
The purpose of this study was to identify gastrointestinal parasites in the small intestine, large intestine, and feces of local pigs from North Sulawesi. Sampling in this study was carried out in Termaal Village, Likupang Barat District, North Minahasa Regency and in Poopoh Village, Tombariri District, Minahasa Regency. Observations and identification of parasites were carried out at the Biology Laboratory of the Faculty of Mathematics and Natural Sciences, UNIMA. Samples of small intestine fluid, large intestine, and pig feces were taken totaling 9 samples. The sample was examined by the Floating Test method, and if parasites were identified, a literature study was carried out with reference to several sources and previous research books to determine the type of parasite species found. The results of this study indicate that all samples observed and identified were positive for the presence of intestinal parasitic worms. The parasitic worms found were Ascaris lumbricoides, Strongyloides ransomi, Trichuris suis, Taenia solium, and Fasciolopsis buski.